A Comprehensive Introduction to Botany - Dollar, Joycelyn, 648122 (Delhi, India : White Word Publications, 2012)
Botany, plant science (s), or plant biology is a branch of biology that involves the scientific study of plant life. Botany covers a wide range of scientific disciplines concerned with the study of plants, algae and fungi, including structure, growth, reproduction, metabolism, development, diseases, chemical properties, and evolutionary relationships among taxonomic groups. Botany began with early human efforts to identify edible, medicinal and poisonous plants, making it one of the oldest sciences. Today botanists study over 550,000 species of living organisms. The term "botany" comes from Greek Botivn, meaning "pasture, grass, fodder", perhaps via the idea of ​​a livestock keeper needing to know which plants are safe for livestock to eat.